Development trend of primary healthcare after health reform in China: a longitudinal observational study - Hui Li; Jie Feng; Zuxun Lu; Yanhong Gong; Xuan Zhou; Guopeng Zhang; Xiaoxv Yin; Jianxiong Wu (BMJ Open)
Objectives Reconstructing the primary healthcare system is the focus of the new round of Chinese health reform. Nevertheless, there have been few studies focusing on the strengthening of primary healthcare in Chinese health system.Design This study was a longitudinal observational study.Primary and secondary outcome measures The data of this study came from China Health Statistical Yearbook (2009–2018). We evaluated the development of primary healthcare based on the absolute values of health resources allocation and health service provision and evaluated the status of primary healthcare throughout the health system based on the composition ratios of the indicators across the health system. The Cochran-Armitage trend test and linear trend test were used to identify the indicators’ trends over time.Results From 2009 to 2018, the amounts of health resources allocation and health service provision of Chinese primary healthcare institutions showed a significant upward trend (p<0.001). However, compared with the indicators in 2009, excepting that the proportion of grants from the government in the whole health system has an upward trend, the proportions of other indicators had an escalating trend in 2018 by 3.66% for practicing (assistant) physicians, by 2.69% for nurses, by 3.99% for total revenues, by 5.87% for beds, by 8.39% for outpatient visits.Conclusion The primary healthcare system has developed rapidly, but its development speed lagged behind the entire health system, resulting in the weakening of its actual functions, which is not in line with the goal of health reform. The government should be more aware of the importance of primary healthcare at all levels of local governments and ensure adequate financial input.